1995
DOI: 10.1111/j.1365-2621.1995.tb09823.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Iron in Lactic Acid Bacteria and Bifidobacteria

Abstract: Lactobacillus acidophilus, L. delbrueckii var. bulgaricus, L. plantarum and Streptococcus thermophilum, all used extensively in the food industry, were tested for their ability to internalize and/or oxidize ferrous iron (Fe2+). For comparison some experiments were performed with bifidobacteria, B. thermophilum and B. breve. All organisms except L. bulgaricus could transport Fe2+ into the cell, where it was partially oxidized to the ferric form (Fe(III)). In addition, L. acidophilus and L. bulgaricus could oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…On the other hand, it has been shown that the presence of heavy metals such as iron induces the process of fat oxidation. Probiotics providing the conditions that cause lead to the release of iron from the tissues thus reducing the oxidation process (Kot, Furmanov, & Bezkorovainy, ). According to the results of this study, Kabploy et al () found that the addition of dietary ANT could decrease lipid oxidation; they suggested that ANT have high anti‐oxidative activity and decreasing MDA in tissue due to their ability to scavenge hydroxyl radical.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been shown that the presence of heavy metals such as iron induces the process of fat oxidation. Probiotics providing the conditions that cause lead to the release of iron from the tissues thus reducing the oxidation process (Kot, Furmanov, & Bezkorovainy, ). According to the results of this study, Kabploy et al () found that the addition of dietary ANT could decrease lipid oxidation; they suggested that ANT have high anti‐oxidative activity and decreasing MDA in tissue due to their ability to scavenge hydroxyl radical.…”
Section: Discussionmentioning
confidence: 99%
“…Although iron effectively reduced dipeptidase activity in pure cultures of P . albensis [ 208 ], the effect may be nullified in rumen fluid as lactobacilli can take up high amounts of iron [ 209 ]. Besides the effects on rumen bacteria, Brade et al [ 210 ] described defaunating effects of zinc-enriched diets in the rumen of dairy cows.…”
Section: Feed Additivesmentioning
confidence: 99%
“…The nature of this bond has been investigated in detail in Bifidobacteria ( Kot and Bezkorovainy 1991; Kot et al . 1994, 1995a; Bezkorovainy and Kot 1998), and it has been suggested that a ferroxidase is used to oxidize ferrous iron which is then stored as Fe 3+ in a particulate locus in the cell. Several factors were identified which could affect this ability (calcium and magnesium content of the growth medium, glucose, lactate, pO 2 and pH) in Bifidobacterium spp., as well as in Lact.…”
Section: Introductionmentioning
confidence: 99%